Post-COVID-19 acquired hemostatic sequelae (Research, Society and Development, 2023)
The exacerbated systemic inflammatory picture generated by COVID-19 is associated with disorders in hemostasis. The objective of this study was to carry out a search, synthesis and discussion about studies related to the consequences of COVID-19 and the hemostatic sequelae generated after SARS-CoV-2 infection. Is a descriptive observational study, of the integrative literature review type. Six studies were included in this research. The COVID-19 causes an inflammatory process associated with hypercoagulability, platelet activation and endothelial dysfunction. The increase in D-Dimer seems to reflect the formation of clots due to viremia and excess cytokines resulting from the inflammatory process. In contrast, persistently elevated D-dimer values even after hospitalization for COVID-19 may not be associated with a risk of VTE (in individuals without risk of thrombosis). Routine treatment of all patients with post-discharge thromboprophylaxis may not be necessary, while targeting high-risk patients may be sufficient. The alteration in the VWF(Ag)/ADAMTS13 axis is related to a prothrombotic state and is very present in patients with COVID-19. There is sustained involvement of endothelial cells, clotting activity, and chronic inflammation over the course of the disease, in addition to potential microvascular damage. The elderly are more susceptible to complications in the course of COVID-19. The majority of the pediatric population has mild and/or asymptomatic cases. However, all age groups are influenced by the presence or absence of comorbidities added with other individual and environmental factors. Care for patients affected by COVID-19 should go beyond hospital discharge, requiring continuous monitoring, evaluation and rehabilitation.